Decentralisation and performance measurement systems in health care - Beazley, Ivor (OECD Working Papers on Fiscal Federalism, 2019)
Based on an OECD survey, this paper presents quantitative and qualitative data on the decentralisation of health systems, focusing on how they vary according to different institutional characteristics and what types of performance measurement systems are used in the health sector. Decision-making in health care tends to rest largely with the central government, which has considerable power across many aspects of the delivery of health services. However, sub-national governments have more control over decisions regarding the inputs, outputs and monitoring of health care services. The majority of OECD countries tends to rely on centralised performance measurement systems, especially to monitor the performance of hospital providers, focusing more on improving performance rather than reducing service costs. Less likely to be monitored under a specific performance framework are providers of ancillary services, retailers and other providers of medical goods, and providers of preventive care